Increased soil pH due to the application of sulfate-reducing bacteria, rhizobia and amendments to acid sulfate soils planted with soybeans. Issue 1 (1st June 2022) - Hanafiah, A S; Haniv, Y; Sarifuddin,; Hidayat, B
Abstract: This study aims to determine the effect of the combination of Sulfate Reducing Bacteria, Rhizobia, and amendment matters on the soil pH acid sulfate soil planted with soybeans, carried out at the Greenhouse, Soil Biology Laboratory, Research Laboratory, Faculty of Agriculture, Universitas Sumatera Utara, from March to September 2021. This study used a factorial randomized block design with 2 factors and 3 replications. Each factor consists of 4 levels. The first factor were H0 (Control); H1 (Sulfate Reducing Bacteria); H2 (Rhizobia bacteria); H3 (Sulfate Reducing Bacteria + Rhizobia Bacteria), and the second factor was B0 (Control); B1 (EFB organic matters doses 15 tons/ha); B2 (EFB organic matters doses 30 tons/ha); B3 (Lime of CaCO3 doses 7.5 tons/ha). The research showed that Sulfate Reducing Bacteria, and Rhizobia were able to increase soil pH significantly. Application of EFB organic matters doses 30 tons/ha, and Lime of CaCO3 doses 7.5 tons/ha can increased soil pH.